PENGARUH FAKTOR EKONOMI, SOSIAL DAN DEMOGRAFI TERHADAP KONTRIBUSI PEREMPUAN PADA PENDAPATAN KELUARGA DI SEKTOR INFORMAL KECAMATAN MELAYA, KABUPATEN JEMBRANA - Kartika Candra Sari Dewi, I Gusti Ayu; Suyana Utama, Made; Marhaeni, AAIN (PIRAMIDA; Vol 12 No 1 (2016), 2016)
The participation of women nowadays is not just demanding equal rights but also their significant role for the development of Indonesian society. The participation of women involves tradition and transitions roles. This study aims to analyze; 1) women’s contribution to family incomes in the informal sector 2) the effect of the level of education, work experience, age, number of dependents and the intensity of adat and religious activities of the outpouring of the working hours of women in the informal sector. 3) the effect of the level of education, work experience, age, number of dependents, the intensity of customary and religious activities as well as the women’s time dedication to family income. 4) the role of the outpouring of the working hours of women in mediating the effect of level of education, work experience, age, number of dependents and the intensity of religious and adat activities of the contribution of women to family incomes in the informal sector in the District Melaya, Jembrana Regency. The data Sources were primary data obtained through direct interviews to women traders and the secondary data were obtained from the Central Bureau of Statistics in Jembrana Regency. The data collection method used was interviews and questionnaires, with the number of respondents as many as 129 people. The analytical tool used was descriptive analysis and path analysis. The results showed the contribution of women was very instrumental in increasing family incomes; women’s contribution to the family income was at an average of 45.53 percent. The level education and the number of dependents had a significant positive effect on the outpouring of working hours of women in the informal sector. The intensity of adat and religious activities had a significant negative effect on the outpouring of working hours of women in the informal sector. Work experience and age did not have a significant effect on the outpouring of the working hours of women in the informal sector. The level of education, number of dependents and the outpouring of hours of work had a significant positive effect on women’s contribution to family incomes in the informal sector. The intensity of adat and religious activities had a significant negative effect on women’s contribution to family incomes in the informal sector. Work experience and age had no significant effect on women’s contribution to the family income. Outpouring of working hours mediated the effect of educational level, number of dependents, as well as adat and religious activities to the contribution of women in the family income. But the outpouring of working hours did not mediate the effect of work experience and age on women’s contribution to the family income in the district of Melaya, Jembrana Reegency.
Keywords: women contribution, outpouring of working hours,informal sector